Challenges to effective breastfeeding among indigenous Ngäbe-Bugle communities in Panama. (20th October 2021) - Ma, B; LaBrot, B; Atkinson, I
Abstract: Background: Panama's overall infant mortality rate is 13.2 deaths per 1000 live births and 28.4 per 1, 000 among indigenous populations such as the Ngäbe-Bugle. 93.8% of the Ngäbe population is impoverished and the cost of formula is prohibitive, resulting in poor substitutes such as cheap sugary beverages. These mothers received little education for breastfeeding and it is understandable why breastmilk 'alternatives' are used. This study explored factors impeding effective breastfeeding in a representative community-based cohort of indigenous Ngäbe-Bugle mothers. This study used the hypothesis that preventable breastfeeding challenges are common and likely negatively impact infant health. Methods: We conducted a closed response and open questionnaire survey of 139 selectively sampled Ngäbe women with 529 live births in 2018-2019. Mothers reported the need for support, use of milk substitutes, and breastfeeding complications such as mastitis. Systemic barriers such as poor access to healthcare professionals were also assessed. Data was analyzed with SAS and Power-BI statistical software by independent statisticians. Results: 71% of mothers stated a need for more support. 32% ceased breastfeeding and used milk substitutes. Latching difficulties (2%), pain (3%), sore, cracked, and bleeding nipples (2%), and mastitis (8%) contributed to cessation. 80% reported no formal education on infant feeding and 83% were unaware of breastmilk benefits. 12% received breastfeeding support from healthcare professionals and 2% received it from a village midwife. Conclusions: Among the Ngabe, lack of knowledge or access to health services contribute to breastfeeding complications and challenges resulting in cessation and the use of poor milk substitutes. Key messages: Breastfeeding initiation and continuation rates are negatively affected by poor education, poor healthcare access, and complications resulting in breastfeeding cessation and milk substitution. Supporting mothers with community-based education and improved healthcare access seems likely to positively impact these challenges to effective infant nutrition.